2006
DOI: 10.1002/jsfa.2639
|View full text |Cite
|
Sign up to set email alerts
|

Drying temperature, endogenous antioxidants and capsaicinoids affect carotenoid stability in paprika (red pepper spice)

Abstract: The major carotenoids and carotenoid esters in Capsicum annuum L. during thermal dehydration of pepper and storage of the ground product (paprika) were examined with special focus on the role of endogenous antioxidants such as vitamins E and C and capsaicinoids, the pungent materials in hot spice red pepper. A high-performance liquid chromatographic (HPLC) method was developed to achieve excellent separation and accurate detection of different carotenoid classes including free xanthophylls, monoesters, caroten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
52
2
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 22 publications
8
52
2
2
Order By: Relevance
“…The report by Daood et al (2006) provided a preliminary but not conclusive investigation on the interaction between capsaicinoid and carotenoids and concluded that to highlight such interactions further studies were needed.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The report by Daood et al (2006) provided a preliminary but not conclusive investigation on the interaction between capsaicinoid and carotenoids and concluded that to highlight such interactions further studies were needed.…”
Section: Resultsmentioning
confidence: 94%
“…10 composition of the molecules of interest (Cervantes-Paz et al, 2014;Daood et al, 2006;Topuz, Dincer, Ozdemir, Feng & Kushad, 2011).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Tai and Chen [14] reported that oven drying resulted in concentration decreases of 42 % for lutein and 48 % for b-carotene when compared with freeze drying. Daood et al [24] did not report any changes in lutein when red peppers (Capsicum annuum L.) were dried at temperatures less than 50°C. Additionally, the concentrations of lutein and b-carotene extracted from spinach and kale leaf tissues decreased &70 % as the drying temperature increased from -25 to ?75°C [25].…”
Section: Cisisomersmentioning
confidence: 98%
“…Materska and Perucka (2005), in evaluating the antioxidant activity of capsaicin and dihydrocapsaicin extracted from C. annuum L., verified by the DPPH method that the antioxidant action of capsaicin was greater than that of dihydrocapsaicin, indicating that the double bond in the lipid chain of capsaicin influenced antioxidant activity. However, Daood et al (2006) found that capsaicinoids have a different impact on the stability of carotenoids depending on maturation and processing conditions. Thus, the higher level of capsaicin in the fresh pepper justifies its higher antioxidant activity compared to peppers subjected to heat treatments.…”
Section: Determination Of the Content Of Phenolic Compounds Antioxidmentioning
confidence: 98%